Energy aware spectrum decision framework for cognitive radio network : a spectrum decision framework for cognitive radio network with energy awareness - Mishra, Vishram (2014)
With the proliferation of pervasive wireless devices and constraining fixed channel allocation policy, there is a contraction in the available and accessible frequency spectrum. Cognitive radios have been proposed to mitigate such problems with opportunistic utilization of the spectral holes in the frequency spectrum which manifests due to the sporadic usage by the licensed users over time and location. Spectrum decision forms one of the intrinsic segment for the operation of cognitive radio network. Thus selection of a channel which has acceptable availability and satisfies the system requirements in terms of bandwidth and power constraints is a task of aerial importance. To this end we propose an energy aware spectrum decision framework for cognitive radio network (ESDF-CR), which guarantees an assured grade of QoS to the system operating on low power, by selecting those channels which require low power for transmission. Techniques including channel selection and packet admission control has been proposed to realize the spectrum decision framework. Performance analysis is done against random channel selection scheme to demonstrate the effectiveness of the proposed framework.